2001
DOI: 10.1086/322611
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Coinfection with Human Immunodeficiency Virus and Hepatitis C Virus in Patients Treated with Highly Active Antiretroviral Therapy

Abstract: A retrospective analysis of data from a cohort of patients coinfected with human immunodeficiency virus (HIV) and hepatitis C virus (HCV) who were treated with highly active antiretroviral therapy (HAART) at 3 infectious diseases units in northern Italy was performed. While the patients were receiving HAART, CD4(+) cell counts significantly increased and HIV RNA serum levels decreased. However, no significant overall changes in alanine aminotransferase (ALT) levels and HCV RNA serum levels were observed. Fifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 27 publications
4
27
1
Order By: Relevance
“…Our results are in conflict with other studies in coinfected patients, which have shown an association between genotype 1 infection and increased quasispecies diversity (38) and HCV load (1,49). However, none of these studies stratified patients based on exposure to HAART.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are in conflict with other studies in coinfected patients, which have shown an association between genotype 1 infection and increased quasispecies diversity (38) and HCV load (1,49). However, none of these studies stratified patients based on exposure to HAART.…”
Section: Discussioncontrasting
confidence: 99%
“…The effect of HAART on HCV load is still controversial. Most studies have shown no change in HCV RNA titers following HAART (11,37,49), although some studies have shown a transient (34,39) or sustained (35) increase in HCV load; yet others have shown a decrease in HCV RNA levels and in some cases even HCV clearance (55).…”
mentioning
confidence: 99%
“…Some studies have shown no significant changes in HCV RNA and alanine aminotransferase serum levels during HAART [73,74]. We have confirmed these results, and we also observed that, in a group of patients who showed increased levels of alanine aminotransferase during HAART, HCV RNA levels did not further increase [75]. In contrast, other investigators reported transient or persistent increases in HCV load during HAART [76,77].…”
Section: Liver Manifestationssupporting
confidence: 88%
“…On the other hand, in a retrospective analysis of data from a cohort of 65 coinfected patients treated with HAART, Torre et al [63] did not report any significant changes in serum transaminase concentrations and HCV viral load during a 3-year follow-up, suggesting that the overall influence of HAART on the clinical course of HCV infection may be limited. The long-term effects of HAART on plasma HCV-RNA levels and transaminase values are summarized in table 1.…”
Section: Effect Of Haart On Hcv-related Liver Diseasementioning
confidence: 95%